WHAT'S TO KNOW ABOUT LABORATORY EXPERIMENTATION IN ECONOMICS? - Feltovich, Nick (Journal of economic surveys, 2011)
Experimental economics has grown as a discipline from near non‐existence 50 years ago to a full‐fledged field within economics in the present. Much of experimental economics research involves experimental methods as a tool, applied to problems in other fields of economics. However, some of this research is inward looking, focusing on questions of the methodology of experimental economics. In this note, I briefly discuss two methodological issues in experimental economics that might benefit from meta‐analysis: the pool from which experimental participants are drawn (university undergraduate students versus other populations) and the scale of monetary incentives faced by participants (large, small or hypothetical).